2015
DOI: 10.1016/j.dnarep.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functional consequences of MUTYH variants associated with colorectal cancer: Damaged DNA affinity, glycosylase activity and interaction with PCNA and Hus1

Abstract: MUTYH is a base excision repair (BER) protein that prevents mutations in DNA associated with 8-oxoguanine (OG) by catalyzing the removal of adenine from inappropriately formed OG:A base-pairs. Germline mutations in the MUTYH gene are linked to colorectal polyposis and a high risk of colorectal cancer, a syndrome referred to as MUTYH-associated polyposis (MAP). There are over 300 different MUTYH mutations associated with MAP and a large fraction of these gene changes code for missense MUTYH variants. Herein, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 66 publications
(130 reference statements)
0
41
0
Order By: Relevance
“…These experiments illustrate that the activity of G382D MUTYH is more dramatically reduced within cells than the in vitro experiments indicated. This may be due in part to the more difficult task of repair in a cellular context [82, 87, 134], as well as other features that may come into play in a cellular context, such as interactions and competition with other proteins [88, 111]. These studies underscore the importance of multiple assays, along with structural studies, to fully explore the functional implications of specific variants.…”
Section: Mutyh-associated Polyposismentioning
confidence: 99%
See 4 more Smart Citations
“…These experiments illustrate that the activity of G382D MUTYH is more dramatically reduced within cells than the in vitro experiments indicated. This may be due in part to the more difficult task of repair in a cellular context [82, 87, 134], as well as other features that may come into play in a cellular context, such as interactions and competition with other proteins [88, 111]. These studies underscore the importance of multiple assays, along with structural studies, to fully explore the functional implications of specific variants.…”
Section: Mutyh-associated Polyposismentioning
confidence: 99%
“…Using a similar approach, Mazzei and co-workers have found that expression of Q324H in cells was associated with 2-fold higher levels of 8-oxoG in DNA, hypersensitivity to oxidants and accumulation of the population in the S phase of the cell cycle [143]. Q324H is found in the IDC of MUTYH, an area of the protein not directly involved in DNA binding or catalysis, but known to facilitate key repair protein interactions with the Rad9-Hus1-Rad1 (9-1-1) complex and APE1 [134]. Q324H was shown to have reduced affinity for Hus-1 of the 9-1-1 complex compared to the WT protein [134, 144].…”
Section: Mutyh-associated Polyposismentioning
confidence: 99%
See 3 more Smart Citations